Salivary interleukin-17 and tumor necrosis factor- in relation to periodontitis and glycemic status in type 2 diabetes mellitus - DOĞAN, BAŞAK (WILEY, 2015)
BackgroundPoorly-controlled glycemic status in type 2 diabetes mellitus (T2DM) is suggested to play a role in the periodontal inflammatory process by aggregating the local cytokine response. Our objectives were to profile salivary interleukin (IL)-17 and tumor necrosis factor (TNF)- levels in subjects with T2DM and to examine their relevance for the periodontal health status and glycemic control levels. MethodsUnstimulated whole saliva samples, together with full-mouth periodontal recordings (plaque index [PI], bleeding on probing [BOP %], gingival index [GI], probing pocket depth [PPD], and clinical attachment level [CAL]), were collected from 123 subjects with T2DM. Additionally, demographic and general health parameters, including fasting blood glucose, glycated hemoglobin (HbA1c), were collected. Salivary IL-17 and TNF- concentrations were analyzed using the Luminex (R)-xMAP technique. ResultsSubjects with poorly-controlled T2DM (HbA1c7) had elevated serum triglyceride (P<0.001) concentration as well as elevated scores of BOP % (P=0.014), PI (P=0.048), GI (P=0.033), and CAL (P=0.003) in comparison to those of well-controlled T2DM (HbA1c<7). When the subjects with detectable salivary IL-17 were categorized in tertiles, the scores of PPD and BOP%, and salivary TNF- concentrations were significantly elevated in the highest (P=0.007, P=0.002 and P<0.001, respectively) and middle (P=0.052, P=0.022, and P=0.003, respectively) tertiles compared to subjects with non-detectable salivary IL-17. The adjusted association between PPD measurements and salivary IL-17 concentrations was significant (P=0.008). ConclusionsPoorly-controlled glycemic status relates to the severity of periodontal disease in T2DM. The association between PPD and IL-17 in saliva, however, is independent from the effect of glycemic status. ?? ??????????????2????(T2DM)?????????????????????????????????T2DM???????????(IL)-17????????(TNF)-???,?????????????????????????? ???123?T2DM?????????????????????(????[plaque index,PI],?????[bleeding on probing,BOP %],????[gingival index,GI],?????[probing pocket depth,PPD]????????[clinical attachment level,CAL])???,??????????????????,?????????????(HbA1c)???Luminex (R)-xMAP????????IL-17?TNF-??? ??????????T2DM???(HbA1c<7)??,??????T2DM???(HbA1c7)???????????(P<0.001),????BOP %(P=0.014)?PI(P=0.048)?GI(P=0.033)??CAL(P=0.003)?????????????IL-17???????,??????IL-17??????IL-17??????3?,??PPD?BOP %???????TNF-????????(??P=0.007,P=0.002?P<0.001)???(??P=0.052,P=0.022?P=0.003)?????????????PPD????????TNF-?????????(P=0.008)? ??T2DM?????????????????????PPD????IL-17??,??,????????????????
Keywords: interleukin-17; periodontal disease; saliva; tumor necrosis factor-; type 2 diabetes mellitus; MATRIX METALLOPROTEINASES; CYTOKINE LEVELS; IL-17; CELLS; PATHOGENESIS; EXPRESSION